Climate Change and Environmental Education: A PlanClima SP 2020-2050 analysis - Aguiar, Denise Regina da Costa; Camargo-Cruz , Paulo Eduardo Alves; Resende, Flávia Grecco (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
This article sought to analyze the Climate Action Plan for the City of São Paulo 2020-2050 (PlanClima SP), published in June 2021, in dialogue with the documents: Curriculum of the City of Natural Sciences and 2030 Agenda. In a critical perspective of Environmental Education, the PlanClima SP establishes some actions towards zero carbon in 2050. In this sense, the objective of the study was to analyze the potentialities presented in the document for the development of sustainable pedagogical practices. The methodology selected for this study was qualitative, carried out with the analysis of the cited documents based on the concept of the Critical Environmental Education. The results found demonstrate practical possibilities for actions aimed at training critical and reflective students for a sustainable development. The Environmental Education actions proposed in the analyzed material point to the modification and construction of behaviors and attitudes aimed at the culture of environmental preservation. It is concluded that the discussion about carbon emissions in a critical and conscious way, through pedagogical practices, is powerful in environmental preservation and sustainability.